Talent management system for financial institutions in Kenya - Michael, Kinuthia Antony (Strathmore University, 2015)
This research aims to provide a solution to the question of talent management for financial institutions in Kenya. The absence of talent management systems has led to financial institutions experiencing retention problems as well as difficulties in succession planning. Applied research was adopted and data was collected through secondary sources such as literature and an interview with managers in the financial sector. Considering the presence of the millennial generation in today's workplace, the solution was based on how to reach them in the environment they are usually found in and applying best practice techniques on rewarding and retaining them. In conclusion, there is a need for the financial institutions to strategize and look into new ways of how to efficiently tap into the talent amongst the millennial generation and establish a sustainable talent pipeline in order to remain competitive in the long run.
Submitted in partial fulfillment of the requirements for the Degree of Master of Science in Information Technology
Keywords: Talent management; Talent management system; Financial institution; Kenya